2021
DOI: 10.3390/ijms222010955
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Amino Acid Transporter 1 Regulates Cancer Stemness and the Expression of Programmed Cell Death 1 Ligand 1 in Lung Cancer Cells

Abstract: The l-type amino acid transporter 1 (LAT1) is a membranous transporter that transports neutral amino acids for cells and is dysregulated in various types of cancer. Here, we first observed increased LAT1 expression in pemetrexed-resistant non-small cell lung cancer (NSCLC) cells with high cancer stem cell (CSC) activity, and its mRNA expression level was associated with shorter overall survival in the lung adenocarcinoma dataset of the Cancer Genome Atlas database. The inhibition of LAT1 by a small molecule in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Many lung cancers show increased expression of ATP1A1 and targeting ATP1A1 with siRNA or drugs (cardenolides) has an antitumor effect [58]. SLC3A2 heterodimerizes with SLC7A5/LAT1, which has a well-established role in lung cancer [59][60][61]. Conversely, our results suggest that erlotinib treatment may result in localization of glycolysis enzymes away from the plasma membrane (Figure 4A).…”
Section: Discussionmentioning
confidence: 75%
“…Many lung cancers show increased expression of ATP1A1 and targeting ATP1A1 with siRNA or drugs (cardenolides) has an antitumor effect [58]. SLC3A2 heterodimerizes with SLC7A5/LAT1, which has a well-established role in lung cancer [59][60][61]. Conversely, our results suggest that erlotinib treatment may result in localization of glycolysis enzymes away from the plasma membrane (Figure 4A).…”
Section: Discussionmentioning
confidence: 75%
“…The levels of S100P mRNA and protein expression are higher in lung cancer, and upregulated S100P increases cancer cell migration and metastasis ( Hsu et al, 2015 ). The levels of SLC7A5 mRNA and protein expression are increased in NSCLC and are correlated with grade, pathologic stage, and OS ( Takeuchi et al, 2010 ; Liu et al, 2021 ). The levels of COL1A1 mRNA expression in lung cancer are increased and are significantly correlated with tumor diameter, metastasis, and OS ( Geng et al, 2021 ; Hou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…GRM1 (glutamine receptor 1), an important receptor of glutamine metabolism pathway, was also overexpressed in lung cancer and promoted tumor development and progression through activating the MAPK and AKT/mTOR pathways [38]. Liu et al demonstrated that the upregulation of LAT1 in pemetrexed-resistant NSCLC cells was correlated with increased cancer stem cell activity, and the inhibition of LAT1 by RNA interference or JPH 203 (a small molecule inhibitor of LAT1) reduced the selfrenewal capability that mediated via the Akt/mTOR pathway [39]. These evidences suggest a relationship between GM and mTOR signaling pathway, which requires further validation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…LAT1 silencing caused the downregulation of programmed cell death 1 ligand 1 (PD-L1) on lung cancer cells. The PD-L1+/LAT1 + subpopulation of NSCLC cells exhibited great Cancer Stem Cell (CSC) activity [39]. In addition, glutamine depletion combination with anti-PD-L1 strongly enhanced antitumor e cacy of T cells by upregulation of Fas/CD95 levels in mice [47].…”
Section: Discussionmentioning
confidence: 99%